Novel Use of Optokinetic Chart Stimulation with a One -Off Epley's Manouvre in a Bed-Ridden, Difficult to Rehabilitate, Care of the Elderly Patient with Undiagnosed BPPV: A Case Report - Benjamin Chitambira (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Background and objective: Unrecognized BPPV leads to activity limitations. This case report aims to report on use of optokinetic chart stimulation and one off Epley's manouvre to treat unrecognised BPPV in chronic Ménière's disease. Methods: This is a single case study in a care of the elderly rehabilitation ward. An 85 year old patient was admitted with abdominal pain, vomiting, clamminess and sweating. She was treated with one off right ear Epley's manoeuvre and daily optokinetic chart stimulation. Results: The Barthel index improved from 5/100 pre-intervention to 50/100 post- intervention and the Elderly Mobility Scale improved from 2/20 to 11/20. Conclusions: Recognising and treating BPPV and co-morbidities in elderly patients is important to ensure treatment is patient-centred, improve cost-effectiveness and reduce unnecessary disability.